La sécurité privée : le phénomène, la contreverse, l’avenir - Cusson, Maurice (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1998)
This article deals with four themes on private security. First, private security is defined as a protection supplied to organizations targeting the specific needs of any given organization. Second, the expansion of private security is seen as resulting from the convergence between a real demand for security and a superior supply than the one offered by the police. Third, the article deals with questions regarding private security involving private live-Finally, it is argued that the future of private security lies in two trends : (1) technologicial integration and (2) sophisticated planning and problem solving.